1985
DOI: 10.1111/j.1365-2621.1985.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional aspects of blood plasma proteins 4. Elucidation of the mechanism of gelation of plasma and egg albumen proteins

Abstract: The mechanism of gelation of plasma and egg albumen proteins in a cake-type model system was elucidated by chemical modification, polyacrylamide gel electrophoresis and electron microscopy. It was demonstrated by chemical modification that gelation via disulphide bonds was predominant in all the plasma and egg albumen proteins. Hydrophobic and hydrogen bonds also prevailed in the plasma protein gels. In contrast the breakdown of hydrophobic and hydrogen bonds increased the strength of egg albumen gels. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Hermansson (1982) found that gelation of BP proteins begins at temperatures above that of meat protein gelation. Howell and Lawrie (1985) reported that below 79 1C BP produced heat reversible gels consisting of linear polymer chains and stabilized by weak non-covalent, hydrophobic and electrostatic linkages. The fact that BP proteins in a meat batter form a gel too late in the process to be integrated into the meat protein gel structure may results in mixed gels which are weaker than gels formed by meat proteins alone.…”
Section: Resultsmentioning
confidence: 99%
“…Hermansson (1982) found that gelation of BP proteins begins at temperatures above that of meat protein gelation. Howell and Lawrie (1985) reported that below 79 1C BP produced heat reversible gels consisting of linear polymer chains and stabilized by weak non-covalent, hydrophobic and electrostatic linkages. The fact that BP proteins in a meat batter form a gel too late in the process to be integrated into the meat protein gel structure may results in mixed gels which are weaker than gels formed by meat proteins alone.…”
Section: Resultsmentioning
confidence: 99%
“…The combined use of dissociating agents have been studied by several researchers (Li & Lee,1996;Sheard, Ledward, & Mitchell,1984), who reported a synergistic effect between SDS and mercaptoethanol based on the combined effect of intermolecular disulfide bond formation and hydrophobic interaction. Howel and Lawrie (1985) reported a considerable reduction in gel strength and breaking strength of whole blood in the presence of mercaptoethanol and urea.…”
Section: Combination Of Dissociating Agentsmentioning
confidence: 97%
“…It has been thought that chemical reagents which block the formation of bond between proteins would provide a means of testing which bonds are involved in aggregate formation and in proteineprotein interactions. For example, mercaptoethanol reduces disulfide bonds, urea and sodium dodecyl sulfate (SDS, CH 3 e(CH 2 ) 11 eSO 4 À Na þ ) break hydrogen bonds between NH and CO groups and hydrophobic interactions, and EDTA (ethylenediaminetetraacetic) acid breaks ionic bonds involving calcium salts (Howel & Lawrie, 1985;Lorient, 1979;Melander & Horvath, 1977;Parnell-Clunies, Kakuda, Irvine, & Mullen,1988). The non-ionic molecules of urea, which binds to water via hydrogen bonds at high concentrations, disrupt the usual aqueous hydrogen-bond network.…”
Section: Introductionmentioning
confidence: 97%
“…Most studies to date have been empirical and have displayed interesting and technologically useful phenomena such as synergistic behaviour to increase the gel strength or foaming properties of proteins or phase separation of protein mixtures which has been applied in the formulation of low fat products (Howell & Lawrie, 1985;Howell & Taylor, 1991). However the exact mechanisms for these interactions are not clear.…”
mentioning
confidence: 99%